Ups and Downs to Become a Professional Teacher: Dynamics of Academic Resilience in Pre-Service Teacher Professional Education Students - Ach. Sudrajad Nurismawan; Raudya Tuzzahra Maghfirani; Atika Ainnur Rahmah; Halimatus Firdiyanti; Fahmia Ayu Lestari; Budi Purwoko (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The consequences of learning and the longer duration of time compared to in-service teacher professional education programs have not received adequate attention from several related parties. In fact, these two things can be supporting factors for pre-service teacher professional education students to be able to successfully complete their studies. This study aims to analyze the dynamics of resilience of professional teacher education (PPG) students. This research is a case study. The subjects of this research involved pre-service students at a private educational university, especially those from the guidance and counseling study program. Data were collected using semi-structured interviews with 7 pre-service teacher professional education students selected based on the characteristics and objectives of the case study. This study is found that the implementation of pre-service teacher professional education for students is very difficult and quite emotionally draining, so that students are required to have good academic resilience. Moreover, in the three dimensions of academic resilience that researchers studied, the average resilience of Pre-Service Teacher Professional Education students is manifested in several activities such as: going for a walk, doing a hobby, confiding in a partner or colleague, crying, and being grateful to manage feelings of stress and negatives emotions that often appear.